PENGARUH INFLASI, NILAI TUKAR DAN TINGKAT SUKU BUNGA TERHADAP INDEKS HARGA SAHAM GABUNGAN (Studi pada Bursa Efek Indonesia Periode 2015-2017) - Linda Amalia Alvian; Chasan Azari; Herman (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2019)
This study aims to determine the effect of inflation, exchange rates (IDR/USD) and interest rates (BI Rate) on the Composite Stock Price Index (CSPI) in Indonesia Stock Exchange from 2015 to 2017. This study uses quantitative method. The data is monthly time series data, from 36 data from January 2015 to December 2017. The data analysis method is multiple linear regression analysis with a significant level of 0.05. The analysis shows that inflation, the exchange rate (IDR/USD) and the interest rate (BI Rate) have a strong relationship with the Composite Stock Price Index (CSPI). Simultaneously the variable inflation, exchange rate (IDR/USD) and interest rate (BI Rate) have an significant effect on the Composite Stock Price Index (CSPI). Partially the inflation variable, exchange rate (IDR/USD) and interest rate (BI Rate) have a negative effect on the Composite Stock Price Index (CSPI).